Pesquisa-ação sobre as formas de promover um aumento na participação dos funcionários no desenvolvimento e uso do sistema de medição de desempenho de uma empresa de bens de capital - Leal, João Batista Sobreira (2009)
The purpose of this essay is to investigate ways to promote an increase at the participation of employees in the development and use of the performance measurement system in an industrial goods manufacturer. Along with economical globalization, several performance measurement models begin to appear and companies in general are brought to invest in the search for the model that better fits each one s purpose. The effort is focused in the development, implementation and use of performance measurement systems. Among a number of proposed models, the one that gained more recognition worldwide was BSC. This fact itself does not guarantee the full use of the performance measurement system. Employee s participation and commitment has been an issue that deserves attention from researchers because it is an unquestionable fact that its involvement increases the performance of the individual and improves the motivation of the group. For this research it was chosen the action-research method, due to the fact of it to allow researchers to play an active role in the very reality of observed facts. The research had the support of large bibliographic studies to identify and evaluate influent factors to development and evolution of SMD. During action-research work, questionnaires were applied, interviews were conducted and thoughts were made about the adopted actions and results achieved. As a final result of field research, a better understanding of process change, skill development in the use of SMD, system management and involvement of stakeholders were achieved. Recommendations resultant of this research included managers, quality management staff and executives of the company, the development of employees, the improvement of SMD use, ownership and continuous improvement of the business.